Dermoscopy of cutaneous lymphangioma circumscriptum - Abhijeet Kumar Jha (Mattioli1885, 2017)
Lymphangiomas are congenital lymphatic malformations. They are clinically characterized by clusters of translucent vesicles, and on dermoscopy, yellow lacunae surrounded by pale septa as well as reddish to bluish lacunae have been described. A young male presented with a seven-year history of a vesicular lesion. Dermoscopy revealed multiple white-yellowish well-circumscribed roundish areas (lacunae) surrounded by pale septa. A few lacunae contained blood, which was characteristically accumulated in the lowest part of the lacuna, resulting in an appearance similar to the so-called “hypopyon” of the eye. We suggest a new “dermatologic” metaphoric term to desrcibe this peculiar feature (half-and-half lacuna).